IMPLEMENTASI PJJ MODA DARING (ONLINE) MAPEL IPS DENGAN MENGGUNAKAN AKUN PEMBELAJARAN PADA MASA PANDEMI COVID-19 KELAS IX A SMPN 1 KANDEMAN - Wulan Dwi Aryani (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2022)
The aims of this study is to : 1) know the implementation of online Learning at Socials Studies. 2) know what factors that are inhibit in implementation of online Learning at Socials Studies.3) know what factors that are support in implementation of online Learning at Socials Studies by using Learning accounts during Covid-19 pandemic. This research was descriptive research, using Sugiyono's design. Data collection techniques were: observation, interviews, and documentation. Data analysis used descriptive qualitative analysis. The results of the study are 1) the Implementation of online Learning at Socials Studies through three activities, namely: planning, implementation and evaluation. In planning the teacher prepared lesson plans, learning media, prepared assessments. In the implementation, the teacher conducted synchronous learning with the Google Workspace for Education such as Google Meet, Slides, Forms and Classroom which are accessed with a learning account. Evaluation activities of students were used to carry out online Learning and submitting assignments online; 2) The inhibiting factors for online Learning were internet networks that were less stable, did not have internet quota, did not have tools such as cell phones or laptops, sometimes cell phone space. not enough to access applications, often forget accounts and passwords @belajar.id; 3) Supporting factors for online learning include the availability of infrastructure in schools such as wifi networks, laptop computers, the ability of teachers to use applications used in online Learning and the government facilitated internet quotas 10 GB free every month to students.